ANJAKAN PARADIGMA ASNAF PENERIMA ZAKAT MELALUI KEFAHAMAN TERHADAP KONSEP PENYUBURAN SECARA IMPLISIT - Mohd Khalid, Halimi; Noor, Zanariah (Journal of Techno-Social, 2012)
Maximize the use of the gift of God s.w.t for raising living standards in ways that comply with Islamic law are very encouraged by Islam. Agenda for the eradication of poverty through the distribution of charity is seen as a very noble effort. Zakat Collection Centre (PPZ) has laid out various means and methods for the realization of the transformation of the character of self-sufficiency of alms to charity is productive. The mechanisms and methods used are seen as realistic and innovative. However, the study made either through observation or study educational materials that have been produced, it appears these efforts have not yet reached a specified percentage. The phenomenon has seen many recipients who receive tithes still have not been able to free themselves and family members out of poverty despite being given every year to help them. Various factors contribute to the cause of the lack of success has been identified. It appears from the assessments made of the transformation of this charity, attitudes and patterns of public opinion has been identified as one of the causes of the failure to optimize the distribution of zakat made by PPZ. It is understandable that people can not understand and appreciate the objectives of the noble efforts made by PPZ. Hence this paper will try to look at this aspect with reference of the understanding of the concept of nourishment among recipients implicit and given less attention than the enrichment of understanding of the concept among the zakat contributer.